Gender violence and self-esteem in women from the Huanja - Huaraz hamlet, 2017 - Castillo Saavedra, Ericson Felix (2018)
Objective: To determine the relationship between gender violence and level of self-esteem in women from the Huanja - Huaraz hamlet, 2017. Materials and methods: A quantitative, prospective, cross-sectional, correlation study. The sample population consisted of 55 women registered as inhabitants of the Huanja - Huaraz hamlet, who met the inclusion and exclusion criteria of the research. For the variables’ analysis and study, previously validated instruments with a reliability of 0.81 were used for both questionnaires. Results: Physical violence accounted for 38.2% of the recorded cases, followed by 29.1%, 14.6% and 18.1% for psychological, sexual and economic violence, respectively. Self-esteem was low in 52.8%, moderate in 43.6%, and high in 3.6%. The Spearman´s rank correlation coefficient (rs) showed a negative and non-significant relationship between the types of violence and self-esteem: physical violence (rs = -0.123, p = 0.371), psychological violence (rs = -0.181, p = 0.186), sexual violence (rs = -0.177, p = 0.195) and economic violence (rs = -0.075, p = 0.589). Conclusions: Physical violence experienced by women from the Huanja - Huaraz hamlet is the most frequent type of violence reported, followed by psychological violence, sexual violence and economic violence. Regarding their selfesteem, women victims of violence feel frustrated, unsuccessful and worthless before society. Therefore, the greater the physical, psychological, sexual and economic violence in women, the lower their self-esteem.